To re-examine the intersection of microglial activation and neuroinflammation in neurodegenerative diseases from the perspective of pyroptosis - Li, Yuan; Li, Ying-Jie; Zhu, Zhao-Qiong (Frontiers in Aging Neuroscience, 2023)
Neurodegenerative diseases (NDs), such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and motor neuron disease, are diseases characterized by neuronal damage and dysfunction. NDs are considered to be a multifactorial disease with diverse etiologies (immune, inflammatory, aging, genetic, etc.) and complex pathophysiological processes. Previous studies have found that neuroinflammation and typical microglial activation are important mechanisms of NDs, leading to neurological dysfunction and disease progression. Pyroptosis is a new mode involved in this process. As a form of programmed cell death, pyroptosis is characterized by the expansion of cells until the cell membrane bursts, resulting in the release of cell contents that activates a strong inflammatory response that promotes NDs by accelerating neuronal dysfunction and abnormal microglial activation. In this case, abnormally activated microglia release various pro-inflammatory factors, leading to the occurrence of neuroinflammation and exacerbating both microglial and neuronal pyroptosis, thus forming a vicious cycle. The recognition of the association between pyroptosis and microglia activation, as well as neuroinflammation, is of significant importance in understanding the pathogenesis of NDs and providing new targets and strategies for their prevention and treatment.